CHARACTERIZATION OF BOTSWANA COAL FROM TWO COAL FIELDS: MABESEKWA AND MMAMABULA TO DETERMINE ITS COAL RANK - MAKOBA, Mmoloki; MOALOSI, Taboka; AGACHI, Paul-Şerban; MUZENDA, Edison; MAMVURA, Tirivaviri A. (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Coal samples from two different coal fields: Mabesekwa and Mmamabula were collected (with six seams from each coal field) to characterize using X-Ray diffractometer (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared (FT-IR) spectroscopy. Proximate and ultimate analysis are also given. Clay minerals kaolinite, pyrite, dolomite, siderite and calcite, and quartz were discovered. Comparing measurements of C, VM, GCV, MC and FC obtained from the samples with literature, Botswana coal identifies as lignite grade A coal suitable for applications in coal gasification and ammonia based fertilisers due to its high volatile matter and high reactivity of char. The paper looks to use different methods to analyse Botswana coal and recommend its potential applications based on literature.